Folk Dress Revitalization as a Component of Language Revitalization: The Case of Wilamowice - Król, Tymoteusz (Ethnographica et Folkloristica Carpathica, 2023)
Although the main goal of language revitalization is keeping a language alive, the expression of ethnic identity and belonging is not exclusively limited to the linguistic phenomenon. In the case of Vilamovians – a small ethnic group living in the town of Wilamowice on the border of Upper Silesia and Lesser Poland, language revitalization has been supported by a group of people wearing the Vilamovian folk dress. This was accompanied by greater engagement of young people learning the Wymysorys language as well to other elements of Vilamovian culture, including the folk dress. In this case revitalization does not mean copying old patterns, but reviving its importance for local community. The Vilamovian folk dress is not limited to the costume of local dance ensemble, it is crucial for ethnic belonging of Vilamovians. The patterns, styles or words (in the case of the language) were less important for them. The reconstructed elements or even whole sets of dress, e.g. the mourning dress, different types of wedding dress and the whole male dress do differ from the historical ones. The ethnographers should not criticize this situation, as it used to be in the past, but focus on their choices and motivations connected to their ethnic belonging. In this text, I have tried to show that the reconstruction/revitalization of a folk dress could proceed in a specific way if combined with language revitalization.